Doxofylline for Pediatric Asthma Steps 1-4. Pediatric Asthma: New Role for an Old Drug - Vincenzo Fierro; Anna Lucia Piscitelli; Edda Battaglia; Alessandro Fiocchi (Frontiers Media S.A., 2022)
The panoply of anti-asthma drugs for children between 6 and 18 years is not limited to those reported in the guidelines. In this review, we will re-assess the role of doxofylline, a xanthine characterized by a much higher handling than that of theophylline, as add-on treatment in pediatric asthma grade 1-4. Ten studies evaluated doxofylline in the treatment of asthma of patients non-responsive to the first-line inhaled corticosteroids. Of these, two included children and one was exclusively pediatric. According to their results, doxofylline exerts a powerful bronchodilator and anti-inflammatory activity, which can be exploited when the inhaled oral corticosteroids are not sufficient to get the desired effect of reducing symptoms. Unlike theophylline, doxofylline does not require blood testing. It can be administered together with or as an alternative to a series of other drugs considered in additional therapy.